A “Second Captain Dreyfus affair”: Joseph Bernstein’s Halifax Experience - Fingard, Judith (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2025)
In 1892 Joseph Bernstein arrived in Halifax, where he shared with other members of the small Jewish community a typical pattern of commercial/trades employment until 1899 when he became an immigration interpreter at the deepwater terminus. His stable work life came to an abrupt halt in 1908 when he was dismissed from the federal government service. At first, he blamed this turn of events on the vindictiveness of five Jewish families involved in a dispute over the suitability of a marriage partner for his third daughter. But when Bernstein delved deeper and realized that his fate was worse than that of two Gentile immigration physicians in Halifax who misbehaved in the same season, he decided that antisemitism had determined his fate. His identification with Alfred Dreyfus may have been inspired by cinematic depictions of the injustice endured by that Jewish French soldier.